Unveiling impact of financial development, renewable energy, and technological innovation on ecological footprint in major remittance-receiving economies – A PQARDL approach - Toumi, Said (International Journal of Renewable Energy Development, 2025)
A nation's financing system is pivotal in fulfilling the demands of sustainable development. Domestic funding sources and international financial flows make substantial contributions to both economic growth and environmental quality, with their influence being of paramount significance. The objective of this study is to analyze the complex linkage between financial development, renewable energy consumption, technological innovation, on ecological footprint in top remittance-receiving economies, namely Indonesia, Bangladesh, Vietnam, Pakistan, Egypt, Mexico, Philippines, China, and India, over the period 1990-2022. Using Panel Quantile Autoregressive Distributed Lag (PQARDL) method, our findings challenge the universal applicability of the Environmental Kuznets Curve (EKC) hypothesis and reveal complex interactions among variables. The long-term empirical results reveal inconsistent relationships between environmental degradation across different quantiles, challenging the universal applicability of the Environmental Kuznets Curve (EKC) hypothesis. Therefore, financial development reveals a mixed impact on ecological footprint across different quantiles, renewable energy consumption advertises a consistently negative association, suggesting its potential as a sustainable development lever. Moreover, technological innovation's influence varies across quantiles, indicating heterogeneous effects on ecological footprint reduction. Therefore, the validity of an inverted U-shaped or N-shaped Environmental Kuznets Curve pointed complexity of income's impact on environmental outcomes. The validity of the N-shaped EKC in all quantiles, acclaiming that policymakers should incorporating renewable energy and technology innovation into respect when formulating environmental calends.